Navigation sensors for mobile robots - Fredriksson, Håkan (Luleå tekniska universitet, EISLAB, 2007)
In mobile robot applications navigation systems are of great importance. Automation of mobile robots demands robust navigation systems. This thesis deals with a few solutions on how to help a mobile robot navigate in an environment. Navigation systems using retroreflective beacons and applications relying on laser range finders are two different solutions to aid a mobile robot. The first type of system provides very robust navigation, with the use of extra infrastructure in the environment. The latter has no need for any extra infrastructure as it can use the structure in the surrounding environment. Navigation using dead reckoning and GPS systems are also discussed. Furthermore, some of the mobile robot platforms available at Luleå University of Technology, and their application are presented. Godkänd; 2007; 20071113 (ysko) CASTT - Centre for Automotive Systems Technologies and Testing